2020
DOI: 10.1002/solr.202000444
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Photoexcited Redox Centers of Semiconductor Photocatalysts for Advanced Synthetic Chemistry

Abstract: Solar photocatalysis is emerging as an environment‐friendly and sustainable energy approach for the production of fine chemicals and pharmaceuticals with high industrial and academic importance. Due to photochemical stability, tunable redox capability, and facile recyclability, semiconductor photocatalysts display remarkable advantages over molecular photocatalysts, thus attracting increasing attention. More importantly, photoexcited hole–electron pairs on semiconductor photocatalysts can accomplish two aligne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 126 publications
(149 reference statements)
0
7
0
Order By: Relevance
“…The conversion of organic pollutants produced by industrial processes such as textile, paint, and printing 1–3 into harmless substances is a major challenge to be explored and solved, which is essential for the health of living organisms and the sustainable development of society. Among the various degradation techniques, photocatalysis 4–7 has been regarded as an ideal method to address the intricate problems of organic pollutant transformation due to its advantages such as environmental friendliness and low energy consumption. 8,9 Early photocatalytic studies primarily focused on conventional semiconductor materials, including metal oxides TiO 2 , 10,11 ZnO, 12,13 metal sulfur compounds CdS, 14 CdSe, 15,16 etc.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of organic pollutants produced by industrial processes such as textile, paint, and printing 1–3 into harmless substances is a major challenge to be explored and solved, which is essential for the health of living organisms and the sustainable development of society. Among the various degradation techniques, photocatalysis 4–7 has been regarded as an ideal method to address the intricate problems of organic pollutant transformation due to its advantages such as environmental friendliness and low energy consumption. 8,9 Early photocatalytic studies primarily focused on conventional semiconductor materials, including metal oxides TiO 2 , 10,11 ZnO, 12,13 metal sulfur compounds CdS, 14 CdSe, 15,16 etc.…”
Section: Introductionmentioning
confidence: 99%
“…A series of recent studies in heterogeneous photocatalysis reveals that proper engineering of the surface by decorating it with metal cocatalysts is crucial to achieve a high performance in H 2 evolution, CO 2 reduction, and synthetic chemistry. 15–28 It has been shown that the metal/semiconductor heterojunction facilitates the charge separation of the photogenerated charge carriers and the storage of free electrons on the metal cocatalyst. 29–31 Additionally, catalytic studies reveal that an optimum adsorption free energy (Δ G ) of photogenerated reactive species ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A series of recent studies in heterogeneous photocatalysis reveals that proper engineering of the surface by decorating it with metal cocatalysts is crucial to achieve a high performance in H 2 evolution, CO 2 reduction, and synthetic chemistry. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] It has been shown that the metal/semiconductor heterojunction facilitates the charge separation of the photogenerated charge carriers and the storage of free electrons on the metal cocatalyst. [29][30][31] Additionally, catalytic studies reveal that an optimum adsorption free energy (ΔG) of photogenerated reactive species (i.e., H atoms, methoxy, and Br • ) on the metal cocatalyst can be achieved by alloying and facet-engineering to boost the kinetics of several photocatalytic reactions (i.e., hydrogen evolution, CO 2 reduction, N 2 fixation).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, a more attractive strategy for the synthesis of imines is the oxidative coupling of amines, in particular, to realize this transformation using abundant solar energy. [ 3 ] The light‐initiated oxidative coupling of amines to produce imines involves the activation of amines by the photogenerated holes to form a carbocationic species, which is followed by a consecutive dehydrogenative coupling of amine to yield imines. [ 4 ] In this process, molecular O 2 acts as the acceptor for photogenerated electrons and consume the surface‐adsorbed H atoms released from the amino groups to push the formation of the imines.…”
Section: Introductionmentioning
confidence: 99%